Genotoxicity and Mutagenicity - Mechanisms and Test Methods 2021
DOI: 10.5772/intechopen.91689
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Future Perspectives of Antimutagenic Agents

Abstract: Mutation is the process leading to heritable changes in DNA caused mainly by internal and external factors. Recently, studies on mutagenic agents have been increased due to increasing in mutation-related disease. The antimutagenic effect is desired to prevent mutation on genes or to inactivate the mutagenic agent. It seems that the interest in antimutagenic substances displaying multiple mechanisms of action will be an important trend in the research and development of new antimutagenic compounds in the near f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, BA was able to lead to ATM activation and a DNA damage response of the cells [62]. The observed antigenotoxicity action by the borenium and borinium compounds (Table 3) could also be attributed to their direct chemical interaction before MMC caused genotoxic damage [64]. Previous evidence exerted that antioxidantfeatured substances can eliminate ROS before these reactive chemicals interact with DNA and change in a DNA sequence [64].…”
Section: Synthesis Of Borinium Ionic Liquidsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, BA was able to lead to ATM activation and a DNA damage response of the cells [62]. The observed antigenotoxicity action by the borenium and borinium compounds (Table 3) could also be attributed to their direct chemical interaction before MMC caused genotoxic damage [64]. Previous evidence exerted that antioxidantfeatured substances can eliminate ROS before these reactive chemicals interact with DNA and change in a DNA sequence [64].…”
Section: Synthesis Of Borinium Ionic Liquidsmentioning
confidence: 90%
“…The observed antigenotoxicity action by the borenium and borinium compounds (Table 3) could also be attributed to their direct chemical interaction before MMC caused genotoxic damage [64]. Previous evidence exerted that antioxidantfeatured substances can eliminate ROS before these reactive chemicals interact with DNA and change in a DNA sequence [64]. Consistent with our findings, previous reports suggested that BCCs have antigenotoxic effects against several genotoxic agents, such as titanium, aluminum, aflatoxins, lead, bismuth, arsenic, and cadmium [65].…”
Section: Synthesis Of Borinium Ionic Liquidsmentioning
confidence: 99%
“…Bio-antimutagens, instead, act after DNA damage, promoting DNA repair or preventing DNA replication [ 84 ]. Antimutagenesis involves different mechanisms, including chemical or enzymatic inactivation of mutagens through the modulation of phase 1 and phase 2 enzymes, prevention of mutagen’s formation, free radical scavenging activity, and antioxidant activity [ 85 , 86 ]. Different studies pointed out that emodin could be classified as a desmutagen agent.…”
Section: Anticancer Mechanisms Of Aqs Isolated From Marine Fungimentioning
confidence: 99%
“…Dietary sources or synthetic compounds that can counteract mutagenic agents as potential anti-mutagens are considered a strategy in cancer chemoprevention and mutation-related diseases. The anti-mutagenic potency, coupled with antioxidant properties, is one of the mechanisms that inhibit mutagenesis [ 23 ]. Our previous study demonstrated the antioxidant ability of chrysin-ES, suggesting that it might exert anti-mutagenic activity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials 2024, 14, 1001 2 of 23 Nanoemulsions, fine oil-in-water dispersions, are both kinetically and physically stable for long periods without gravitational separation, flocculation, or coalescence. Nanoemulsions are currently used to administer several medicines, including pharmaceuticals, phytopharmaceuticals, cosmeceuticals, dietary drugs, and nutraceuticals, to improve human health [8].…”
Section: Introductionmentioning
confidence: 99%